An experimental examination of alcohol consumption, alcohol expectancy, and self‐blame on willingness to report a hypothetical rape. Issue 3 (15th December 2017) - Flowe, Heather D.; Maltby, John
Abstract : This study experimentally examined the role of victim alcohol intoxication, and self‐blame in perceiving and reporting rape to the police using a hypothetical interactive rape scenario. Participants ( N = 79) were randomly assigned to consume alcohol (mean BAC = 0.07%) or tonic water before they engaged in the scenario. Alcohol expectancy was manipulated, and participant beliefs about the beverage they thought they had consumed and their feelings of intoxication were measured. Alcohol consumption and expectancy did not affect the likelihood that the nonconsensual intercourse depicted in the scenario was perceived and would be reported as rape. Participants with higher levels of self‐blame were less likely to say they would report the hypothetical rape. Self‐blame levels were higher for participants who believed they had consumed alcohol, and were associated with increased feelings of intoxication. The implications are discussed.